Genotypic variation in grain nutritional content and agronomic traits of upland rice: strategy to reduce hunger and malnutrition - Ferrari, Samuel [UNESP]; Cunha, Matheus Luís Oliveira [UNESP]; do Valle Polycarpo, Gustavo [UNESP]; Zied, Diego Cunha [UNESP]; de Oliveira, Lara Caroline Alves [UNESP]; Júnior, Enes Furlani [UNESP] (Springer Nature, 2022)
Hidden hunger, known as micronutrient deficiency in humans, affects about 2 billion people worldwide. One of the ways to minimize hidden hunger is through genetic biofortification. This study aimed to evaluate the natural genotypic variation of micronutrients in upland rice grains and agronomic traits to select genetic material for further agronomic and genetic biofortification aiming high density of micronutrients in grains. The experimental design used was randomized blocks, with treatments consisting of 8 upland rice genotypes. The agronomic traits and the content of iron, zinc and copper in the rice genotypes grains were evaluated. The genotypes OSVR15001, OSVR15029, OSVR15038 and OSVR15047 did not differ statistically from the commercial cultivar IAC 203 in the two agricultural years and can be used as a complement in the production of upland rice. The OSVR15047 genotype maintained high Cu content in the grains and elevated grain yield in the two years of cultivation, being able to be used in genetic improvement for the emergence of superior genotypes. The OSVR15042 genotype was the only one that maintained a high Zn concentration in the grains in both years, also being able to be used for genetic biofortification. Our results contribute to the selection of genotypes that have good yield and good nutritional content in grains, which can help to minimize the effects of hidden hunger and increase the health of the population.
Keywords: Biofortification; Cupper; Iron; Oryza sativa L; Panicles; Zinc